Neutral and charged inter-valley biexcitons in monolayer MoSe2 - Kai Hao (Nature Portfolio, 2017)
Atomically thin transition metal dichalcogenides host excitons and trions, however higher-order states, although possible, are difficult to identify experimentally. Here, the authors perform polarization-resolved coherent spectroscopy to unveil the signature of neutral and charged inter-valley biexcitons in monolayer MoSe2.